Cover Image, Volume 86, Issue 5. Issue 5 (16th April 2018) - Gaines, J. C.; Acebes, S.; Virrueta, A.; Butler, M.; Regan, L.; O'Hern, C. S.
Abstract : The cover image, by J. C. Gaines et al., is based on the Research Article Comparing side chain packing in soluble proteins, protein‐protein interfaces, and transmembrane proteins, DOI:10.1002/prot.25479 .